The utilisation and feasibility study of solid waste, palm kernel cake, and trichantera gigantea (ketum ayam) as animal feed for broiler - Muhammad Amirul Syafiq, Nasarudin; Abdul Syukor, Abd Razak; Ali Zainal-Abidin, Mohamad Termizi; Nurul Farah Anisa, Hairolnizam; Farah Amalina, Ishak; Suryati, Sulaiman; Mohd Rashid, Ab Hamid; Noraini, Samat (Penerbit UMP, 2024)
This study aims to investigate the utilisation and feasibility of solid waste into animal feed. Every year, agro-based industries produce a large number of residues. Since the majority of untreated and underutilised agro-industrial wastes, this problem can be solved by utilising the waste from palm oil industry into animal feed. The waste that are used in this study is palm kernel cake (PKC). PKC is one of the region's most abundant, accounted 2.3 Million tonnes are being export and potentially to be used as low-cost agricultural products. Furthermore, it has the potential to mitigate the pollution levels and reduce the operational expenses associated with waste management. The solid waste characteristics in PKC proven that these by-products are high in nutrient that can be used for animal feed with the additional of Trichantera Gigantea (Ketum Ayam) and other ingredients to help the growth rate of chickens and also control the agro-industrial waste.